Tecnologías que se utilizan para apoyar la enseñanza de la asignatura de inglés: Una revisión sistemática de literatura. - Terán, Álvaro P. (2022)
Knowing how to support English learning with technologies that facilitate it is very important for teachers of different levels. Teachers can apply strategies that help optimize the time that learners are exposed to this new language. The objective of this article is to identify the technologies used for teaching English as a second language, through a systematic review of literature with studies published between January 2018 and June 2021 in studies carried out in Iberoamerica. This systematic literature review has been based on the methodology proposed by Kitchenham (2007). It was done with the objective of systematizing in an organized way the studies found about technologies that are used to support the teaching of English as a second language. Then the phases were followed, established by Kitchenham, through the use of planning methods and techniques, review, and presentation of results. In this way, the results (16) were analyzed and classified according to their year of publication, country where they were investigated, keywords presented in each article, technological tools used, teaching strategies, academic level of the investigated students, skills developed in students, and the advantages and disadvantages of using technological tools. In this study, the technologies used in the teaching of English as a foreign language, like WhatsApp, Moodle and Web Learning English, that stand out, they were identified in order to provide teachers with useful resources and strategies to be used in face-to-face, distance, and extracurricular learning.